The effect of solution-focused approach on social adjustment and solution-focused thinking skills in nursing students who experienced violence in childhood: a single group pre-test-post test study - Hümeyra Hançer Tok; Ebru Akbaş; Selma Sabancıoğulları (BMC Nursing)
Abstract Background Individuals who are exposed to violence during childhood may experience social adjustment problems, depression, substance abuse, and other psychosocial issues in adulthood. This situation can also negatively affect societal harmony. Nursing students, due to the nature of their profession, work in high-stress environments and may be more vulnerable to the effects of childhood trauma. The solution-focused approach [SFA] is a method that aims to enhance social adjustment and problem-solving skills by focusing on individuals’ strengths. Objective The aim of this study is to examine the effect of the solution-focused approach on social adjustment and solution-focused thinking skills in nursing students who experienced violence during childhood. Method The research was conducted with 24 nursing students from a university’s nursing department. A 7-session solution-focused social adjustment program was applied to the participants. Social adjustment and solution-focused thinking skills were evaluated using scales before and after the program. The Wilcoxon Signed-Ranks Test was used for data analysis. Results After the solution-focused approach, a significant decrease in social adjustment scores and a significant increase in solution-focused thinking skills were observed among the students. The short-term decrease in social adjustment scores may be explained by the emotional activation triggered during the intervention process, where participants -especially those with unresolved childhood trauma- began confronting painful memories and reevaluating their social relationships. These results indicate that SFA is effective in improving social adjustment and problem-solving skills. Conclusion The solution-focused approach can be considered an effective method for enhancing social adjustment and solution-focused thinking skills in nursing students. However, it is suggested that additional psychosocial support mechanisms may be needed to ensure the sustainability of gains, especially in individuals with a history of childhood trauma. Clinical trial number Not applicable.